BERPIKIR ALJABAR SISWA SMP DALAM MENYELESAIKAN MASALAH OPEN-ENDED MATEMATIKA - Ayu Syahidah Fatimah; Masriyah; Agung Lukito (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
In preparing for Indonesia Emas 2045, the development of superior human resources has become a top priority, with education as a fundamental pillar. 21st-century skills (4C) and NCTM mathematics standards demand the development of higher-order thinking skills, including algebraic thinking. Algebraic thinking is a fundamental element of mathematical reasoning involving pattern recognition, generalization of mathematical relationships, and abstraction. However, various studies show that Indonesian students' algebraic thinking ability remains low, as reflected in the 2018 PISA scores below the OECD average. Algebra instruction still focuses on procedures and symbol manipulation, with minimal use of challenging open-ended problems. Whereas open-ended problems with multi-solution and multi-strategy characteristics can naturally train students' algebraic thinking. This study aims to describe the algebraic thinking of eighth-grade junior high school students with high and low mathematical abilities in solving open-ended mathematics problems. This research uses a qualitative descriptive approach. Research subjects were selected using purposive sampling technique based on the results of the Mathematics Ability Test (TKM), teacher recommendations, and student willingness. The instruments used include TKM to group students into high and low ability categories, Problem-Solving Tasks (TPM) in the form of open-ended problems measuring algebraic thinking, and semi-structured interview guidelines to explore students' thinking processes in depth. Data analysis techniques use the Miles, Huberman, and Sadana model consisting of data condensation, data display, and conclusion drawing.